(untitled) (Scientific journal of the Fergana State University, 2023)
This article is devoted to teaching military training students the basics of civil protection in the Republic of Uzbekistan, improving their knowledge of emergencies, the main stages of its development; elimination of possible emergencies on the territory of the Republic, using the example of specific emergencies; training in modern types of weapons of mass destruction and their effects and protection against them, as well as fostering in students patriotism, resilience and confidence in their abilities, in emergency situations, and the development of students’ profound knowledge, skills and abilities in civil defence.